About one of the types of predicates expressing emotional states - Dyszak, Andrzej S. (Papers in Linguistics, 2025)
The article concerns sentences constituted (formally and semantically) by causative predicates that are exponents of an emotional state, implying the causal event of this state and connoting the exponents of this event in such a way that they always open a position in the nominative case for a noun representing either a predicate of the causal event, e.g. Wymachiwanie (kijem przez Jana) straszy Piotra [Brandishing (a stick by John) scares Piotr], or its argument (if the agent’s exponent of the causal event appears in this position, e.g. Jan straszy Piotra [John scares Piotr], then the predicate opens a position in the instrumental case for the predicate’s exponent, e.g. Jan straszy Piotra wymachiwaniem (kijem) [John scares Peter by brandishing (a stick)], or for the exponent of an argument other than the agent, e.g. Jan straszy Piotra kijem [John scares Peter with a stick]). Appropriate verbs (both imperfective, e.g. bulwersować [outrage], emocjonować [thrill], podniecać [excite], and perfective, e.g. rozgoryczyć [embitter], wzburzyć [outrage], zawstydzić [put someone to shame]) that can be considered emotional were excerpted (based on their definitions containing one of the nouns: emocja [emotion], uczucie [feeling], namiętność [passion]) from Uniwersalny słownik języka polskiego [Universal Dictionary of the Polish Language]. Dictionary examples of their use (sentences or their transformations) were used to illustrate ways of expressing a causal event in sentences with causative predicates, which are ultimately proposed to be called state-causative predicates in order to distinguish them from the corresponding (non-causative) state predicates, which can also express emotional states, e.g. Ktoś boi się czegoś [Someone is afraid of something], Ktoś emocjonuje się czymś [Someone is excited about something] (in both sentences, the nominative component has the semantic function of the subject = the patiens of the state expressed by the predicate).